Nurcholish Madjid's Neo-Modernism in Substantive Islamic Movements in Indonesia - Yufriadi, Ferdi; Syahriani, Fadilla; Afifi, Abdullah A (IDRIS Darulfunun Institute, 2023)
At this time, there is a stagnation of thought among Muslims regarding whether the concept of an Islamic state is still being debated or not. Islamic socio-political movements are divided into two streams, namely Substantive Islam and Symbolic Islam. Nurcholish Madjid firmly rejects the politicization of Islam in the interests of political groups that are members of Islamic parties. With the motto: